Об устойчивости стационарных движений сферического маятника, взаимодействующего со струной - Лила, Д.М. (Прикладная механика, 2010)
It is obtained the equation of motion of the hybrid model of one mechanical system. The system consists of horizontally situated string and spherical pendulum, which is hung up in some point of the string. The conditions of asymptotic stability of stationary motions of the spherical pendulum, which is interacted with elastic string, are established.